Herding behavior and sentiment: pre and post-investor domicile code closure in Indonesia stock exchange - Subhiksa, Siwa Kantha; Wibowo, Buddi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Previous research has shown mixed results regarding herding behavior in Indonesia. Furthermore, this article analyzes herding behavior in the Indonesian capital market, especially in the conditions before and after the closure of the investor's domicile code as of June 27 2022, by the Indonesian Stock Exchange (IDX). This regulation concerns the closing of foreign and domestic broker codes, which are considered capable of causing herding behavior. Additionally, investor sentiment was also reviewed as a factor that might be contributed to the mixed results of herding behavior in Indonesia. A sample of 607 companies before domicile code closure and 681 companies after domicile code closure were tested using a combination of CSSD and CSAD. The two approaches used to measure show non-significant results of herding both pre and post-closure of domicile code. Investor sentiment was also not seen as a factor that contributed to herding since herding is also non-significant during low or high sentiment before and after the domicile code's closure. Different methods and influencing factors should be considered for further research.